PERLINDUNGAN HUKUM BAGI PEMOHON KREDIT DENGAN MENGACU PADA ASAS KESEIMBANGAN ANTARA PELAKU USAHA (BANK) DAN KONSUMENNYA (PEMOHON KREDIT) - Sri Suryaningsih, Ni Luh Putu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2012)
Banking institutions as one of the financial institutions have a strategic role in supporting the economic life of a country. Banking institutions meant here as an intermediary of the parties who have surplus funds to the lack of funds. Banking activities that provide services on the economic sector that do not in spite of the risks that could harm the banks themselves and the customer. Relationship between the bank and the customer is bound to a credit agreement unnoticed by the debtor of his rights is often overlooked by the bank. Guaranteeing the law protection and law certainty for the debtors losing for such unilateral, the regulations of consumer protection, therefore, have important functions. The type of research used in this paper is the normative legal research. This research moved from the inclusion of the standard clause that would open up opportunities for businesses, especially banks to position the client, in this case the credit applicant, to be weaker than the bank.
Keywords: bank (bank); perlindungan konsumen (consumer protection)